(untitled) (Social Science Review, 2025)
Abul Bashar—a ride-hailing driver from Dhaka—commented, “Uber allowed me to be my boss. Even if I drive throughout the day, no one has the right to rush or demand anything of me.” Despite such perception of flexibility, analyzing narratives of platform workers gathered in August 2020 and February 2021, in this article, it is argued that platform workers endure more stress providing their services than non-platform workers, such as driving for a private employer, because customer preferences change with every new trip. Additionally, they must work longer hours to be eligible for bonuses, and in any disputes, the platforms consider “passengers/customers are always right.” The article also reveals how digital platforms (ride-hailing or delivery) establish a coercive mechanism through their passengers’/customers’ rating system. Thereby, the article debunks the myth of democratization of work and revolutionizing the transportation/service system, identifying the affective regimes of work—that produce no material and durable goods but immaterial goods, such as comfort and ease for the customers—in digital platforms at Dhaka. Moreover, emphasis on affective labor and incentives results in disjunctive temporalities linked with family life and social routines, engendering modes of embodiment that constitute digital platform workers. Finally, the article argues that the affective regime generates forms of alienation and sociality that are co-implicated rather than opposing each other. Social Science Review, Vol. 41(1), June 2024, Page 195-214.